Research Progress of Postoperative Recurrence of Chronic Subdural Hematoma in Chinese and Western Medicine - Liu, Xue; Fan, Xiaoxuan (Journal of Contemporary Medical Practice, 2025)
This review summarizes the risk factors associated with recurrent CSDH, including patient-specific factors, imaging factors, surgical factors, and pharmacological factors, while exploring the mechanisms underlying CSDH recurrence from the perspective of Traditional Chinese Medicine (TCM) theory. Aging is inextricably linked to CSDH, and the integration of TCM and Western medicine, along with anti-aging strategies, represents an effective approach to preventing CSDH recurrence.